2015
DOI: 10.1111/bjep.12089
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between teacher burnout and student motivation

Abstract: The dimensions of teachers' burnout might play different roles in the transmission from teachers to students. Teachers' status of burnout is an important environmental factor associated with students' quality of motivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
200
1
22

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(234 citation statements)
references
References 35 publications
11
200
1
22
Order By: Relevance
“…Burnout was linked to job-related neurasthenia [2], depression [8] and voice disorder [9]. A study found that teachers' status of burnout as an essential environmental factor is associated with students' autonomous motivation [10]. In addition, burnout of preschool teachers hurt teacher-child interaction [11].…”
Section: Introductionmentioning
confidence: 99%
“…Burnout was linked to job-related neurasthenia [2], depression [8] and voice disorder [9]. A study found that teachers' status of burnout as an essential environmental factor is associated with students' autonomous motivation [10]. In addition, burnout of preschool teachers hurt teacher-child interaction [11].…”
Section: Introductionmentioning
confidence: 99%
“…Educators that suffer from burnout have decreased classroom organization and a diminished ability to model emotional regulation. Educators who experience higher levels of emotional exhaustion facilitate less student motivation, impacting academic outcomes (Shen et al, ), deleteriously impacting the students they serve. Studies have shown emotions to be contagious, and educators that lack the coping skills to deal with stressful environments are less capable of attending to student demands as they are limited in their emotional capacity (Jennings & Greenberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Educators that suffer from burnout have decreased classroom organization and a diminished ability to model emotional regulation. Educators who experience higher levels of emotional exhaustion facilitate less student motivation, impacting academic outcomes (Shen et al, 2015), deleteriously impacting the students they serve.…”
mentioning
confidence: 99%
“…The persistent interest in the identification and appraisal of those factors constituting a fertile ground for the occurrence of burnout may be explained through the severity of the outcomes that this phenomenon could trigger. Specifically, teachers' burnout has been shown to impair students' motivation [4], to negatively affect students' personal development and academic success [5]. A large body of research on the antecedents of teacher burnout contributed to shedding light on the characteristics of this professional field that can precipitate burnout symptoms.…”
Section: Introductionmentioning
confidence: 99%